Retailer corporate branding / Sharifah Faridah Syed Alwi - Syed Alwi, Sharifah Faridah (Faculty of Business and Management ; UiTM Press, 2007)
The personification approach (e.g. customers view company name as a person) has been used in the past to understand corporate brand image (CBl). However, empirical studies using this approach were limited to only a few settings (e.g. department store and automobile). The applicability of this type of methodological approach is questioned due to its limited empirical findings. The present study enhances this understanding by providing the empirical evidence in the context of retail bookstore. The research is informed by 511 responses from experienced shoppers. Structural equation modelling was performed to identify the bookstore's CBL While previous literatures stress consumers appeared to express department stores to be more agreeable, chic and ruthless, the study found that the bookstore's appeared to be expressed as more agreeable, competent and enterprise. The practical contribution of the study and its managerial implications can be seen in the context of defining strategy and positioning the corporate brand in book retailing context.